Unusual Imaging Appearance of a Huge Intracranial Dermoid Cyst Located Across the Anterior and Middle Skull Base - Wang, Xuejian; Yu, Yong; Zhang, Xiaobiao; Hu, Fan; Gu, Ye; Xie, Tao; Yu, Hao; Cai, Zhenhua (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Intracranial dermoid cysts are rare congenital neoplasms. Typical dermoid cysts are well-circumscribed fat-density masses with no associated contrast enhancement. We report a woman with a dermoid cyst across the anterior and middle skull base of unusual imaging appearance. This report highlights the challenge facing the diagnosis and management of intracranial dermoid cysts with unusual primary imaging findings.
Keywords: dermoid cyst; unusual imaging appearance; anterior and middle skull base